Unraveling the Plasma Protein Corona by Ultrasonic Cavitation Augments Active‐Transporting of Liposome in Solid Tumor. Issue 9 (1st January 2023) - Wang, Guowei; Jiang, Yifan; Xu, Junjun; Shen, Jiaxin; Lin, Tao; Chen, Jifan; Fei, Weidong; Qin, Yating; Zhou, Zhuxian; Shen, Youqing; Huang, Pintong
Abstract: Ligand/receptor‐mediated targeted drug delivery has been widely recognized as a promising strategy for improving the clinical efficacy of nanomedicines but is attenuated by the binding of plasma protein on the surface of nanoparticles to form a protein corona. Here, it is shown that ultrasonic cavitation can be used to unravel surface plasma coronas on liposomal nanoparticles through ultrasound (US)‐induced liposomal reassembly. To demonstrate the feasibility and effectiveness of the method, transcytosis‐targeting‐peptide‐decorated reconfigurable liposomes (LPGLs) loaded with gemcitabine (GEM) and perfluoropentane (PFP) are developed for cancer‐targeted therapy. In the blood circulation, the targeting peptides are deactivated by the plasma corona and lose their targeting capability. Once they reach tumor blood vessels, US irradiation induces transformation of the LPGLs from nanodrops into microbubbles via liquid–gas phase transition and decorticate the surface corona by reassembly of the lipid membrane. The activated liposomes regain the capability to recognize the receptors on tumor neovascularization, initiate ligand/receptor‐mediated transcytosis, achieve efficient tumor accumulation and penetration, and lead to potent antitumor activity in multiple tumor models of patient‐derived tumor xenografts. This study presents an effective strategy to tackle the fluid biological barriers of the protein corona and develop transcytosis‐targeting liposomes for active tumor transport and efficient cancer therapy. Abstract : A transcytosis‐targeting peptide‐decorated reconfigurable liposome (LPGL) is capable of ultrasound‐induced liposomal reassembly and protein‐corona decortication. Ultrasound irradiation induces size‐transformation of the LPGL and decorticates the surface protein corona by lipid membrane reassembly, whereby the capability to recognize the receptors on tumor neovascularization is regained, ligand/receptor‐mediated transcytosis is initiated, and efficient tumor accumulation and penetration is achieved, leading to potent antitumor activity.